Epifanii Slavinetskii's Greek-Slavonic-Latin Lexicon between East and West by Walter Riggs Thompson (review). - Vakareliyska, Cynthia M. (Journal of Slavic Linguistics)
This work focuses on the Greek-Slavonic-Latin Lexicon (GSL) compiled by the 17th-century Ruthenian monk Epifanij Slavineckij, examining its creation, use, and reception through linguistic, historical, and lexicographic perspectives. The study challenges previous views by arguing that Slavineckij was not a Graecophile but incorporated significant Latin influence, including Slavic calques from Latin and Western European sources, and that the draft manuscript employs a variant of Ruthenian Church Slavonic later Russified in Muscovite copies. The dissertation provides detailed paleographic and grammatical analyses of the draft manuscript, explores its sources among contemporaneous Greek-Latin dictionaries, and discusses the development of an academic vocabulary within the lexicon. While exhaustively researched and meticulously presented, the work’s structure and depth may be challenging for readers outside specialized fields such as lexicography and Slavic linguistics.